Book reviews: Nouriel Roubini, Stephen Mihm, Crisis Economics: A Crash Course in the Future of Finance - Cristian, Uţă (Annals of Spiru Haret University. Economic Series, 2010)
Many years ago, professor Nouriel Roubini got the Dr. Doom nickname. He was one of the few economists warning that the entire world economy was on the verge of a major recession, unseen since the Great Depression. As immediate cause, he identified the speculations spreading in the United States that finally led to the bankruptcy of the investment banks. In 2007, his predictions came true. Suddenly, Roubini’s voice started to be heard.